Respuesta :

NotNav

Step-by-step explanation:

To give you a hand for this question, I will show you how to work out one of the equations

One equation is [tex]y - 1 = \frac{-5}{4} (x-2)[/tex]

We know that when x = -2, y = 6

So we can substitute in -2 and see if we get 6

[tex]y - 1 = \frac{-5}{4} (-2-2)[/tex]

[tex]y - 1 = \frac{-5}{4} * (-4)[/tex]

[tex]y - 1 = 5[/tex]

[tex]y = 5 + 1[/tex]

[tex]y=6[/tex]

So this equation is true! Now try the same for the other equations :)

Answer:

Step-by-step explanation:

Ver imagen xenia168